Hydrogen storage in lithium, sodium and magnesium-decorated on tetragonal silicon carbide. (9th July 2021) - EL Kassaoui, Majid; Houmad, Mohamed; Lakhal, Marwan; Benyoussef, Abdelilah; El Kenz, Abdallah; Loulidi, Mohammed
Abstract: Motivated by the widespread application and fascinating properties of various silicon-carbon nanomaterials, we have extensively investigated the properties of tetragonal silicon carbides (t-SiC) monolayer as a novel 2D material for hydrogen storage. Using calculations of the density functional theory comprising van der Waals interactions of type vdW-DF2-C09x, the structural stability, electronic properties and hydrogen molecules adsorption energies on the surface of pure t-SiC were investigated. The results show that adsorption energies of H2 molecules in this system are stronger than that of graphene. We also found that the decoration with alkali (Li, Na) and alkaline-earth (Mg) metals atoms increases the stability of hydrogen compared to the pure system. The studied system decorated with 8 elements of Li/Na/Mg is able to adsorb up 24 molecules of hydrogen and reaches a gravimetric capacity of 6.50, 5.54 and 5.48 wt%, respectively. The desorption temperatures found are significantly high compared to other 2D systems. Highlights: Based DFT/vdW study of H2 storage was performed in t-SiC monolayer. t-SiC system has stronger adsorption energy than graphene and Tgraphene. Li/Na/Mg decoration enhances the hydrogen molecule storage properties on t-SiC. 8Li@t-SiC system can absorb up to 6.50 wt% as a hydrogen gravimetric capacity. Desorption temperature exceed substantially the critical point of hydrogen.